Emotional responses to auditory hierarchical structures is shaped by bodily sensations and listeners’ sensory traits - Minatoya, Maiko; Daikoku, Tatsuya; Kuniyoshi, Yasuo (Frontiers in Psychology, 2025)
Emotional responses to auditory stimuli are a common part of everyday life. However, for some individuals, these auditory-induced emotions can become distressing enough to interfere with daily functioning. Despite the prevalence of these experiences, the mechanisms underlying auditory-induced emotional responses remain only partially understood. Previous research has identified several contributing factors, including features of the auditory stimuli, listener traits, and bodily sensations triggered by the stimuli. However, prior studies have primarily focused on the acoustic features of auditory stimuli, leaving the role of syntactic features largely unexplored. This study focuses specifically on hierarchical syntactic structures, examining how they influence emotional experiences in conjunction with listener traits and bodily sensations. We conducted an online experiment in which 715 participants listened to 26 sound sequences, each of which systematically varied in hierarchical syntactic structure. The sequences were generated by combining three types of local pitch movement with three types of global pitch movement, each presented in ascending and descending pitch directions, resulting in nine levels of combined complexity. Participants rated the emotional valence and arousal of each sequence and indicated any bodily sensations they experienced using a bodily map. Measures of sensory processing patterns were also collected. Results showed that emotional valence was associated with the complex interplay of moderate syntactic complexity (“not too simple, not too complex”), sensory sensitivity, and upper torso sensations. These findings contribute to existing research by identifying syntactic features that shape auditory-induced emotional experiences and by demonstrating the association between bodily sensations and emotional experience.